2017
DOI: 10.1007/s00134-017-4756-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of ultrasound-guided infra-clavicular cannulation of the subclavian vein in cardiac surgical patients: short-axis versus long-axis approach

Abstract: The short-axis procedure for ultrasound-guided subclavian cannulation offers advantages over the long-axis approach in cardiac surgery patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 24 publications
0
27
2
3
Order By: Relevance
“…A recent RCT reported that the success rate of ultrasound-guided central venous catheterization in the subclavian vein was significantly higher when using SA than when using LA [ 23 ], which seems contradictory to our results. We speculate that the differences could be due to methodology: the procedure was performed 1) in real patients and 2) not by a novice operator.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent RCT reported that the success rate of ultrasound-guided central venous catheterization in the subclavian vein was significantly higher when using SA than when using LA [ 23 ], which seems contradictory to our results. We speculate that the differences could be due to methodology: the procedure was performed 1) in real patients and 2) not by a novice operator.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, the goal of our study was to assess the anatomy surrounding the axillary vein and not the feasibility of echo-guided subclavian access per se. In a recent study by Vezzani et al 8 of 190 patients, the authors observed a 100% success rate in cannulation when performed by experienced anesthesiologists. In addition, they showed more complications using a long-axis compared to a short-axis approach.…”
Section: Limitationsmentioning
confidence: 97%
“…In the internal jugular vein (IJV) subgroup, 17 , 20 , 22 , 23 the total success rate was also no different between the SA-OOP and LA-IP groups (RR, 1.00; 95% CI, 0.98–1.02; P =0.99; I 2 =0%; Figure 3 ) and the TSA also confirmed the result (the cumulative Z-curve crossed the futility boundary and entered the futility area; Figure 4B ). Only one study 25 was included in the subclavian vein (SCV) subgroup, and the results show that the SA-OOP approach was more efficacious than the LA-IP approach in increasing the total success rate (RR, 1.23; 95% CI, 1.10–1.38; P <0.01; Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%